2015
DOI: 10.1038/aps.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the pharmacological mechanism of the Chinese formula Huanglian-Jie-Du decoction in the treatment of ischemic stroke using a systems biology-based strategy

Abstract: Aim: Huanglian-Jie-Du decoction (HLJDD) is an important multiherb remedy in TCM, which is recently demonstrated to be effective to treat ischemic stroke. Here, we aimed to investigate the pharmacological mechanisms of HLJDD in the treatment of ischemic stroke using systems biology approaches. Methods: Putative targets of HLJDD were predicted using MetaDrug. An interaction network of putative HLJDD targets and known therapeutic targets for the treatment of ischemic stroke was then constructed, and candidate HLJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…HLJDD acted as a potential neuroprotective agent and offered protection on ischemic injury (Hwang et al, 2002; Wang et al, 2014; Zhang et al, 2015). However, the optimal proportions and combinational mechanisms of HLJDD on the treatment of ischemic stroke remain unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…HLJDD acted as a potential neuroprotective agent and offered protection on ischemic injury (Hwang et al, 2002; Wang et al, 2014; Zhang et al, 2015). However, the optimal proportions and combinational mechanisms of HLJDD on the treatment of ischemic stroke remain unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroactive ligand–receptor pathway includes many G-protein-coupled receptors, which are often located on the cell surface and involved in the transduction of an endogenous signal into an intracellular response 49. G-protein-coupled receptors regulate vital processes by controlling the expression and function of seven transmembrane receptors, which play a particularly important role in some widespread neurological disorders 19. For example, the activation of the A1 adenosine receptor in allergic rabbit airway smooth muscle causes the production of inositol 1,4,5-trisphosphate [Ins(1,4,5)P3] via a pertussis toxin-sensitive G protein-coupled phospholipase C. This signaling mechanism may be involved in the generation of contractile responses.…”
Section: Resultsmentioning
confidence: 99%
“…(Gan Cao [GC]) – were collected from the Chinese Academy of Sciences chemistry database (http://www.organchem.csdb.cn/scdb/main/slogin.asp, updated on July 20, 2015). This database displays chemical information, including chemical and crystal structures, spectra, reactions, syntheses, and thermo-physical properties 19. The available structural information for YHQFC included 29 compounds in MMH, 12 compounds in BTLZ, 7 compounds in KXR, 34 compounds in ZBM, 24 compounds in PPY, 1 compound in SSG (as CaSO 4 ⋅2H 2 O), 18 compounds in SCP, 14 compounds in DQY, 35 compounds in XJYZH, 7 compounds in CSL, 89 compounds in WWZ, 55 compounds in YXY, 78 compounds in ZS, and 190 compounds in GC.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al demonstrated that Chang'an II protected the intestinal mucosa against post-inflammation irritable bowel syndrome (PI-IBS) through integrated effects of immunomodulation, anti-inflammation, and anti-anxiety [13] . In two articles by Zhao et al [14] and Zhang et al [15] , the contributions of different parties in Fangjis to the total action of Fangjis were demonstrated. Though each single herb (Ramulus Cinnamomi, Guizhi; Paeonia lactiflora, Shaoyao; Rhizoma Anemarrhenae, Zhimu) could affect some diabetic peripheral neuropathy (DPN)-related functions and pathways, GuizhiShaoyao-Zhimu decoction showed more effects on those DPNrelated functions and pathways, such as aryl hydrocarbon receptor signaling and apoptosis signaling [14] .…”
mentioning
confidence: 99%
“…Though each single herb (Ramulus Cinnamomi, Guizhi; Paeonia lactiflora, Shaoyao; Rhizoma Anemarrhenae, Zhimu) could affect some diabetic peripheral neuropathy (DPN)-related functions and pathways, GuizhiShaoyao-Zhimu decoction showed more effects on those DPNrelated functions and pathways, such as aryl hydrocarbon receptor signaling and apoptosis signaling [14] . A network analysis of the ingredients in Huanglian-Jie-du Decoction revealed their putative targets in ischemic stroke-related pathway systems [15] . With a rational combination of compounds diverse functions with different combined modes may emerge for the therapeutic purpose.…”
mentioning
confidence: 99%